The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/nano11082149
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Role of Synthesis Conditions on the Structure of Zinc Oxide-Reduced Graphene Oxide Nanofillers

Abstract: The diversity of zinc oxide (ZnO) particles and derived composites applications is highly dependent on their structure, size, morphology, defect amounts, and/or presence of dopant molecules. In this work, ZnO nanostructures are grown in situ on graphene oxide (GO) sheets by an easily implementable solvothermal method with simultaneous reduction of GO. The effect of two zinc precursors (zinc acetate (ZA) and zinc acetate dihydrate (ZAD)), NaOH concentration (0.5, 1 or 2 M), and concentration (1 and 12.5 mg/mL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 70 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, ZnO nanostructures were grown in situ with simultaneous reduction of GO sheets by a solvothermal method using ethanol as solvent. The obtained ZnO-rGO nanostructures can be used as functional fillers due to the antimicrobial activity of ZnO [42]. Narayanan et al [25] also reported the hydrothermal synthesis of rGO using starch as reducing agent.…”
Section: Green Chemical Reductionmentioning
confidence: 99%
“…Furthermore, ZnO nanostructures were grown in situ with simultaneous reduction of GO sheets by a solvothermal method using ethanol as solvent. The obtained ZnO-rGO nanostructures can be used as functional fillers due to the antimicrobial activity of ZnO [42]. Narayanan et al [25] also reported the hydrothermal synthesis of rGO using starch as reducing agent.…”
Section: Green Chemical Reductionmentioning
confidence: 99%
“…41 Different synthetic methodologies have been adopted to synthesize nanocomposites, but hydrothermal method can be distinguished due to its high efficiency, controllable morphologies, uniformity and growth, low cost, easy processing, and eco-friendly nature as it does not use any hazardous solvent. 42,43 Thus, in this research work, hydrothermal synthesis method has been used to prepare rhinestone sheet like nanocomposites using CDs, ZnO, and rGO. It has been proposed that CDs and ZnO nanoparticles have been attached onto the rGO nanosheets during the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…However, the DPs of GO are not clearly identified for the prepared samples. This can be attributed to the addition of a small amount of graphene during the synthesis process as well as the low-diffraction intensity of GO sheets [17]. The crystallite size "L" of the prepared samples is calculated using the Scherrer equation as mentioned in the previous work [18].…”
Section: Structural Analysesmentioning
confidence: 99%